Acoustic Characteristics of Bamboo-based Guitar – A Case Study - Aaliyawani E., Sinin; Sinin, Hamdan; Khairul Anwar, Mohamad Said; Ahmad Faudzi, Musib; Khairil Anwar Dean, Kamarudin; Hairul Hafizi, Hasnan (North Carolina State University, 2025)
Bamboo is a fast-growing plant easily obtained in Malaysia. It is commonly used for constructing various solid structures including the guitar. Its unique sound quality makes it different from the traditional wooden guitar. The Yamaha guitar sound was used as reference for the generally preferred guitar characteristics. This work focused on the acoustic characteristics easily obtained using the frequency spectrum analysis via a PicoScope oscilloscope and spectrogram using Adobe Audition. A microphone was used for recording the string sound and yielding the frequency response function. The Fast Fourier Transform (FFT) spectra showed that the Yamaha guitar had less partials compared to the bamboo guitar, except string 4. Strings 1, 2, and 3 showed a regular signal from the Yamaha guitar whereas the bamboo guitar showed an irregular pattern with significant overtone. The intensity of the partials in the bamboo guitar displayed a recognizable pattern, i.e., a reduction of partial intensity amplitude proportional to increasing frequency in strings 4, 5, and 6. Some random partials appeared between the harmonics in string 1, 2, and 3 from bamboo guitar whereas the absence of partials in the Yamaha guitar could be due to the higher radiation coefficient of wood, which displays a different timbre.